Engineering Yarrowia lipolytica to produce advanced biofuels: Current status and perspectives. (December 2021) - Lu, Ran; Cao, Lizhen; Wang, Kaifeng; Ledesma-Amaro, Rodrigo; Ji, Xiao-Jun
Graphical abstract: Highlights: Fatty acid- and terpene-derived biofuels are ideal advanced transportation fuels. Y. lipolytica is a valuable chassis for the overproduction of advanced biofuels. Engineering Y. lipolytica to overproduce advanced biofuels is urgently needed. Engineering strategies in Y. lipolytica for advanced biofuel overproduction are summarized. Future perspectives in Y. lipolytica advanced biofuel production are prospected. Abstract: Energy security and global climate change have necessitated the development of renewable energy with net-zero emissions. As alternatives to traditional fuels used in heavy-duty vehicles, advanced biofuels derived from fatty acids and terpenes have similar properties to current petroleum-based fuels, which makes them compatible with existing storage and transportation infrastructures. The fast development of metabolic engineering and synthetic biology has shown that microorganisms can be engineered to convert renewable feedstocks into these advanced biofuels. The oleaginous yeast Yarrowia lipolytica is rapidly emerging as a valuable chassis for the sustainable production of advanced biofuels derived from fatty acids and terpenes. Here, we provide a summary of the strategies developed in recent years for engineering Y. lipolytica to synthesize advanced biofuels. Finally, efficient biotechnological strategies for the production of these advanced biofuels and perspectives for future research are also discussed.